(untitled) (Research, Society and Development, 2023)
This paper aimed to describe the prevalence of dental caries in Quilombola schoolchildren aged 5 to 12 years using the DEF-T (decayed, extracted and filled teeth) and DMF-T (decayed, missing and filled teeth) indices. A cross-sectional study. The sample consisted of 47 schoolchildren, aged between 5 and 12 years old, of both sexes, in a municipal school located in a Quilombola community in the Tocantins state (Brazil). The participants underwent a clinical oral examination, performed by a dentist. Despite the relatively low rates (DEF-T at 5 years of 1.5 and DMF-T at 12 years of 1.24), the prevalence of caries was 78.72%, being higher in males than in females. In addition, only 5.4% of schoolchildren with some experience of caries received restorative treatment. In conclusion, the prevalence of caries in Quilombola schoolchildren aged 5 to 12 years was 78.72%, while the DEF-T/DMF-T index was 2.85 (± 2.84) for females, and 3.71 (± 3.52) for males.